Beyond the Chalkboard: Digital Innovations in Islamic Learning through Interactive PowerPoint - Nurdin, Nurdin; Anhusadar, Laode; Lubis, Maesaroh; Hadisi, La; Rijal, Mohammad (Jurnal Ilmiah Peuradeun, 2024)
In the Gen Z era, innovative and creative methods are essential for effective Islamic education. During that period, students are granted internet connectivity and portable digital devices, which facilitate the acquisition of knowledge about Islam. This study developed a novel interactive learning medium using PowerPoint Office 2010, focusing on Aqidah Akhlak’s curriculum implementation. Employing the ADDIE model as the research and development (R&D) strategy, the study involved validation by experts and practical assessments by teachers and students. The selected research instruments comprised expert validation sheets and media practicality assessments. The impact was computed with descriptive statistics. The results indicated high validity, with scores of 85% from material experts, 82.4% from media experts, and 87% from design experts. The practicality tests revealed 98% and 89.17% approval ratings from teachers and students, respectively. The effectiveness of the medium was demonstrated by a significant improvement in student performance, with pre-test and post-test scores of 69.70 and 85.29, respectively. These findings affirmed the impact of the developed interactive media on enhancing student learning outcomes in Islamic education.